Porcine Transmissible Gastroenteritis Virus - ODEND'HAL, STEWART (The Geographical Distribution of Animal Viral Diseases, 1983)
This chapter provides an overview of porcine transmissible gastroenteritis virus (TGE). This virus is a species that belongs to the family Coronaviridae and the genus Coronavirus. The virus causes severe fatal diarrhea in young piglets and usually a mild disease in adult pigs. Pigs, foxes, dogs, and cats are the hosts to the virus. TGE was first described in 1946 in the United States. Subsequently, it was found to be in many other countries. Live vaccines have been used for porcine transmissible gastroenteritis. Epizootiological studies that have been made on the disease reveal that it is possible that birds are involved as carriers of the disease. A profusion of methods of diagnosis has been reported in the literature for the disease. Agar gel immunodiffusion (AGID), virus neutralisation (VN), indirect immunofluorescent assay (IFA), complement fixation (CF), microneutralization, and enzyme-linked immunosorbent assay (ELISA) are some diagnostic techniques for the disease.